FUNGSI SISTEM INFORMASI AKUNTANSI PERSEDIAAN DALAM MENUNJANG PENGELOLAAN PERSEDIAAN ALAT- ALAT MEDIS DI DINAS KESEHATAN KABUPATEN NIAS - PARNINGOTAN SIMANJUNTAK (LP2MTBM MAKARIOZ, 2020)
This research is conducted in the Health office of Nias District which is located at Jl. Kartinin 1 No. 7 Gunungsitoli NiasRegency North Sumatera, Telp. 0639-21134, fax. (0639)-21462. The health office is an organization that engages in thehealth sector. Health Service requires a wide range of resources, one of the most important is the provision of medical toolsbecause of the provision of medical tools that are not smooth will impede health services in Puskesmas-Puskesmas. Thisresearch aims to determine the function of information system of inventory accounting in supporting the management ofmedical equipment supplies in the health office of Nias District, and to know the management of medical equipment suppliesconducted in the health office of Nias District. Based on the discussion of research results known that ordering system orprocurement of goods/services in the health office of Nias District is done online so as to improve and guarantee efficiencyand effectiveness, as well as ordering medical tools is done openly so that there is no fraud or evasion of medical tools forpersonal benefit, and the management of medical equipment supplies has been supported by the presence of adequateinventory accounting information system so that the management of medical equipment supplies can be held quiteeffectively. Data processing is also used by computers that can process data quickly and risk making mistakes smaller. Thenthe author can draw conclusions that the function of information system inventory accounting that applied to the health officeof Nias District has been sufficiently support in the achievement of the management of medical equipment supplies in thehealth office of Nias District.